Blattlaus-Schlupfwespen der Sammlung F. P. Müller, Rostock (Hymenoptera: Ichneumonoidea; Aphidiidae). - Mackauer, Manfred (Contributions to Entomology = Beiträge zur Entomologie, 1962)
This paper deals with the aphid parasites (Hymenoptera: Ichneumonoidea, Aphidi-idae) of the collection of F. P. Müller at the Deutsches Entomologisches Institut. Fiftyeight parasite species are recorded from a total of 104 different host aphids of the families Lachnidae, Callipteridae, Thelaxidae, and Aphididea (Homoptera: Aphidoidea), most of which were collected in Central Germany. Geographical distribution and host range are given for each species. Aphidius ervi Haliday ssp. nigrescens Mackauer, n. ssp., Aphidius tanacetarius Mackauer, n. sp., and Trioxys chaitaphidis Mackauer, n. sp., are described as new. In addition, Aphidius picipes (Nees 1811) is redescribed, and a neo-type is fixed for this species. Nomenclatural Actspicipes (Nees, 1811) (Aphidius), Neotype described as Bracon picipestanacetarius Mackauer, 1962 (Aphidius), spec. n.nigrescens Mackauer, 1962 (Aphidius ervi), sspec. n.chaitaphidis Mackauer, 1962 (Trioxys), spec. n.